2019
DOI: 10.5204/ssj.v10i3.1407
|View full text |Cite
|
Sign up to set email alerts
|

Supporting First-Year Students During the Transition to Higher Education: The Importance of Quality and Source of Received Support for Student Well-Being

Abstract: The present exploratory study evaluated perceptions of actual support received in relation to stress and well-being among first-year students attending Canadian and U.S. higher education institutions (N = 126). Given that traditional assessments of received support account only for how often support was received, the present research examined unique effects of support quality in addition to frequency with respect to four distinct sources of support (family, friends, faculty/staff, institution). Following from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
5

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 26 publications
2
41
0
5
Order By: Relevance
“…In addition to the sociodemographic and academic variables analyzed above, we tried to understand the impact that students' perceptions about the transition from secondary to higher education, and their options regarding the course, can have on the level of burnout, considering that the transition experience is an imminent cause of stress during the first year of post-secondary studies [28]. In fact, it was proven that there are differences in the manifestations of academic burnout due to the students' perception about the negative impact of the sudden freedom brought by the transition from secondary education to higher education, thus validating hypothesis 12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the sociodemographic and academic variables analyzed above, we tried to understand the impact that students' perceptions about the transition from secondary to higher education, and their options regarding the course, can have on the level of burnout, considering that the transition experience is an imminent cause of stress during the first year of post-secondary studies [28]. In fact, it was proven that there are differences in the manifestations of academic burnout due to the students' perception about the negative impact of the sudden freedom brought by the transition from secondary education to higher education, thus validating hypothesis 12.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it was proven that there are differences in the manifestations of academic burnout due to the students' perception about the negative impact of the sudden freedom brought by the transition from secondary education to higher education, thus validating hypothesis 12. Students who consider that this freedom has affected them in a negative way have higher levels of burnout, as [28] refer. Freedom brings responsibility and, in this sense, young people may not yet be mature enough to properly manage emotions, relationships and even studies, without a support network as tight as up until then; that is, there are lower levels of emotional intelligence and resilience that, as mentioned earlier, act as a kind of protection against the syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this was financial stress (Kift, 2015; Quality Indicators for Learning and Teaching, 2020 ). On the other hand, student success in the first year of study contributes to ongoing retention and success ( Maymon et al, 2019 ; Schütze, 2021). It has been shown that success can be enhanced by supporting the transition of specific skills such as self-efficacy and self-regulation yet often not identified as prerequisites for course admission ( Hailikari et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that success can be enhanced by supporting the transition of specific skills such as self-efficacy and self-regulation yet often not identified as prerequisites for course admission ( Hailikari et al, 2019 ). As described by Maymon et al (2019) , the tertiary sector must create environments where all learners can succeed. From a review of relevant literature, it is evident that a gap likely exists between some students’ expectations versus experiences; but the precise nature of this gap has not yet been investigated ( Crisp et al, 2009 ; Maymon et al, 2019 ; Schütze, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Colleges are working to keep up with this demand as well as address the issue in other ways. For example, First Year Experience (FYE) or similar seminar courses can help with general transition issues [5] and may add modules on topics that address some of these issues specifically.…”
Section: Introductionmentioning
confidence: 99%